2017
DOI: 10.1111/jam.13369
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a potential antibacterial lead structure against bacterial biofilms among new naphthoquinone compounds

Abstract: Since vancomycin is one of the last treatment options currently available, and it is unable to inhibit biofilm, the research of new antimicrobials is urgent. In this context, 2-hydroxy-3-phenylsulfanylmethyl-[1,4]-naphthoquinones proved to be a promising lead structure against MRSA and bacterial biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 66 publications
(101 reference statements)
0
14
1
Order By: Relevance
“…Droserone, 3-chloroplumbagin, plumbagin, and its isomer ramentaceone ( Figure 1 ) are the most prevalent naphthoquinones synthesized in tissues of plants of the Droseraceae family ( Juniper et al, 1989 ; Kreher et al, 1990 ; Gaascht et al, 2013 ; Krychowiak et al, 2014 ). The antibacterial activity of most of NQs concerns mainly Gram-positive bacteria like S. aureus , as most of Gram-negative bacteria are intrinsically resistant to NQs ( Riffel et al, 2002 ; Krolicka et al, 2008 , 2009 ; Moreira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Droserone, 3-chloroplumbagin, plumbagin, and its isomer ramentaceone ( Figure 1 ) are the most prevalent naphthoquinones synthesized in tissues of plants of the Droseraceae family ( Juniper et al, 1989 ; Kreher et al, 1990 ; Gaascht et al, 2013 ; Krychowiak et al, 2014 ). The antibacterial activity of most of NQs concerns mainly Gram-positive bacteria like S. aureus , as most of Gram-negative bacteria are intrinsically resistant to NQs ( Riffel et al, 2002 ; Krolicka et al, 2008 , 2009 ; Moreira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical study of the relationship between the electronic structure and the activity of the P2X7R receptor from a series of 2-hydroxy-1,4-naphthoquinone derivatives, using the quantitative structure-activity relationship (QSAR) method was done. 52) The results showed that there are specific zones of these naphthoquinone derivatives potentially involved in the biological process. The presence of the different substituents seems not to have direct participation in the interaction; their importance may be associated with the modification of the electronic structure of the common skeleton.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 96%
“…Based on the analysis of the results, a corresponding two-dimensional pharmacophore was proposed. 51,52) 2.5. Antimicrobial Activity There are on-going studies on the antimicrobial activity of 1,4-naphthoquinones in relation to various microbial pathogens that are dangerous as sources of fatal diseases, epidemics and nosocomial infections.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…The antibacterial activity of 6a and its derivatives 7a, 7b, and 7c was tested as previously described using paper disks impregnated with each compound 13 . The derivatives were also analyzed quantitatively using microdilution assays in 96-well inert polystyrene microtiter plates (Nuclon; Nalge Nunc International, Rochester, NY, USA) to determine the minimal inhibitory concentration (MIC) 14 .…”
Section: Susceptibility Testsmentioning
confidence: 99%